Incipient sediment motion with upward seepage - Chiew, Yee-Meng (2012)
This study investigates the effect of upward bed seepage on the critical condition of incipient sediment motion in open channel flow both analytically and experimentally. The critical condition was derived by analyzing the forces acting on a sediment particle lying on a permeable horizontal bed subject to seepage. The ratio of the critical shear velocity with seepage to that without seepage depends on the ratio of the hydraulic gradient of seepage to its critical value under the quick condition. Experimental results concerning incipient motion of cohesionless uniform sediments in open channel flow show that for a particular size of sediment, the critical shear velocity decreases with increasing seepage velocity. All measurements generally support the theoretically derived expression of the critical shear velocity in the presence of an upward seepage.